Comparative skin transcriptome analysis as a potential tool to investigate intra- and inter-population differences in belugas - Unal, Ebru; Singh, Vijender; Suydam, Robert; Goertz, Caroline E. C.; Romano, Tracy A. (Frontiers in Marine Science, 2024)
As long-lived top predators inhabiting the Arctic and subarctic, belugas are under threat of anthropogenic stressors including climate change, pollution, noise, and habitat degradation, which in turn can negatively affect their health and viability. There is currently a need for health indicators that can be easily collected and used to assess and monitor the response to stressors in whales. Comparative transcriptomics using skin tissue can be used to provide understanding of organismal responses to stressors at the cellular level. For this study, intra-and inter-population comparisons were performed using the skin transcriptomes obtained from Bristol Bay (BB) belugas sampled in spring and late summer, and Eastern Chukchi Sea (ECS) belugas sampled in early summer in Alaska to investigate significantly differentially expressed genes over 2-fold change (padj<0.05). Both principal component and hierarchical clustering analysis showed separate clustering of ECS whales, with further clustering of BB whales based on season. Intra-population comparisons carried out between different sexes and age groups did not result in any significant changes. However, the samples collected in spring versus summer within BB stock resulted in 541 significantly regulated genes, with significant activation (z-score≥|2|) predictions in pathways related with extracellular matrix organization, collagen biosynthesis and degradation, wound healing and cytokine signaling, potentially suggesting epidermal changes occurring in preparation for the seasonal molt in BB whales. The inter-population comparisons performed separately for BB-Spring versus ECS and BB-Summer versus ECS resulted in 574 and 938 significantly regulated genes, respectively. The significantly enriched canonical pathways common to both comparisons suggest increased cell survival and host defense responses along with increased cellular maintenance and growth in BB whales, and increased inflammation in ECS whales. These changes observed could potentially be due to differences in molting, bias in hunting preferences and/or differences in environmental conditions during the time of sampling. Findings from this study suggest comparative skin transcriptomics as a useful tool towards understanding biologically relevant gene expression differences at different temporal and spatial scales among beluga stocks with potential to inform and contribute to conservation and recovery of endangered beluga stocks.